Macro-to-nanoscale investigation of wall-plate joints in the acorn barnacle Semibalanus balanoides: correlative imaging, biological form and function, and bioinspiration. Issue 157 (7th August 2019) - Mitchell, R. L.; Coleman, M.; Davies, P.; North, L.; Pope, E. C.; Pleydell-Pearce, C.; Harris, W.; Johnston, R.
Abstract : Correlative imaging combines information from multiple modalities (physical–chemical–mechanical properties) at various length scales (centimetre to nanometre) to understand the complex biological materials across dimensions (2D–3D). Here, we have used numerous coupled systems: X-ray microscopy (XRM), scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), optical light microscopy (LM) and focused ion beam (FIB-SEM) microscopy to ascertain the microstructural and crystallographic properties of the wall-plate joints in the barnacle Semibalanus balanoides . The exoskeleton is composed of six interlocking wall plates, and the interlocks between neighbouring plates (alae) allow barnacles to expand and grow while remaining sealed and structurally strong. Our results indicate that the ala contain functionally graded orientations and microstructures in their crystallography, which has implications for naturally functioning microstructures, potential natural strengthening and preferred oriented biomineralization. Elongated grains at the outer edge of the ala are oriented perpendicularly to the contact surface, and the c -axis rotates with the radius of the ala. Additionally, we identify for the first time three-dimensional nanoscale ala pore networks revealing that the pores are only visible at the tip of the ala and that pore thickening occurs on the inside (soft bodied) edge of the plates. The pore networks appear to have the same orientation as the oriented crystallography, and we deduce that the pore networks are probably organic channels and pockets, which are involved with the biomineralization process. Understanding these multiscale features contributes towards an understanding of the structural architecture in barnacles, but also their consideration for bioinspiration of human-made materials. The work demonstrates that correlative methods spanning different length scales, dimensions and modes enable the extension of the structure–property relationships in materials to form and function of organisms.